Embracing Sustainability in Purchase Behavior Using the Theory of Planned Behavior - Azura Rizkiatami; Yolanda Masnita; Kurniawati Kurniawati (MIX: JURNAL ILMIAH MANAJEMEN, 2023)
Objectives: The purpose of this paper is to examine factors influencing consumer green purchase behavior towards international and local sustainable and slow-fashion brands in Indonesia. The fashion industry contributes 10% of total carbon emissions globally. Indonesia itself is a country ranked second in contributing water pollutant damage caused by textile production. The growth of fast fashion trends threatens the environment and the planet. But, public awareness of sustainable and slow fashion is beginning to rise. This study aims to further analyze factors influencing green purchase behavior. The theory of planned behavior was developed to examine consumer sustainable consumption behavioral intention. Methodology: Online questionnaires were distributed to people who had already purchased one of the sustainable brands in Indonesia at least once in their life. 283 data were collected but only 240 of which were able to fulfill the criteria of the study. Data analysis used Smart PLS 3.2.8.Finding: Environmental knowledge, eco-label, environmental advertisement, and green trust positively influence green purchase behavior. Environmental advertisement positively influences environmental knowledge, and environmental knowledge and advertisement positively influence eco-label. Green trust is not a mediating influence between environmental knowledge and green purchase behavior.Conclusion: This study's finding is that consumer awareness and recognition of sustainable fashion adoption is rising. People are starting to worry about textile production and consumption that harm the environment.